Didactic conditions for the formation of technical competences of university students - Nauryzbayeva, G.K.; Gabdullina, G.L.; Rystygulova , V.B. (Recent Contributions to Physics, 2023)
This paper discusses the issue of organizing professional-oriented training (POT) in physics for students of the educational program "Power Engineering" in order to form students' technical competencies, which are extremely necessary and important in the process of performing professional tasks in the future. The article presents the didactic conditions for the formation and development of technical competencies of university students, an example of a professionally oriented lecture on the topic of physics with an emphasis on the electric power industry, tasks for independent work of a student with technical content. Selected laboratory works on the considered topic of the section of mechanics are shown, which are necessary for fixing the lecture material. Particular attention is paid to the organization of the student's research work - attracting students to an effective, informative, and most importantly - professionally oriented research work of the student. The effectiveness of the organization of POT in physics is shown.